Factors associated with complications during pregnancy - Zeidan, muna (Iraqi National Journal of Nursing Specialties, 2015)
Objective (s): To determine factors associated with the pregnancy complications (Maternal age, education, obstetrical history, gravidity, birth space interval, and smoking). Methodology: A cross-sectional study conducted at Al- washash & Bab-almoadham primary health care centers. The sample was (non probability convenient sample) which included (550) pregnant women. The study started from 1st April 2014 to 1 st of April 2015. The data was collected by direct interview using special questionnaire to obtain socio-demographic information. Results: the result shows that mean age of the subjects was 26.5± 4.39 years, 57.8% were housewives, the sample included 103 premature uterine contractions, 98 pregnancy induced hypertension , 90 urinary tract infection , and 80 anemic . Analysis of results by logistic regression test shows that (maternal age , gravidity, gestational age , birth space interval , and smoking ) were significant factors associated with pregnancy complications. Recommendations: health education to all attending pregnant women in MCH centers about risk of complications during pregnancy